Prosthodontic management of angle class III malocclusion with a maxillary single complete denture and mandibular partial denture: A case report - Ahmad Masruri; Meliana (Indonesia Prosthodontic Association, 2025)
Background:Angle Class III malocclusion presents a challenge in prosthodontic rehabilitation, especially when a maxillary single complete denture must oppose a partially dentate mandibular arch. Achieving acceptable esthetics and function requires careful planning of the occlusal scheme, tooth position, and vertical dimension, particularly in patients who refuse or are unsuitable for orthodontic or orthognathic treatment. Case Report: This case report describes the prosthodontic management of a 63-year-old male patient with Angle Class III malocclusion, presenting with a completely edentulous maxilla and a partially edentulous mandible. The patient’s chief complaint was poor esthetics due to reverse overjet, sunken lip support, and disharmonious smile appearance, compounded by functional difficulties in mastication. A maxillary single complete denture and a mandibular removable partial denture were planned to correct anterior esthetics while maintaining a stable and functional occlusion. Conclusion:In patients with Angle Class III malocclusion who decline or are not candidates for orthodontic or surgical correction, careful prosthodontic planning with a maxillary single complete denture opposing a mandibular partial denture can provide satisfactory esthetic and functional outcomes. A case-based, individualized approach is essential to respect the underlying skeletal pattern while optimizing dental and facial esthetics. Keywords:Angle Class III malocclusion; single complete denture; removable partial denture; esthetic rehabilitation; occlusal scheme; prosthodontic management.